2012
DOI: 10.1080/17470218.2011.652969
|View full text |Cite
|
Sign up to set email alerts
|

Licking and Liking: The Assessment of Hedonic Responses in Rodents

Abstract: Affective processes are a key determinant of behaviour: At its simplest, liked stimuli are approached while disliked stimuli are avoided. Although assessing hedonic responses in nonverbal animals can be difficult, one relatively tractable approach relies on detailed analyses of rodents' consummatory behaviour. Rodents typically produce rhythmic sets of licks that can be grouped into clusters on the basis of the intervals between licks. The mean number of licks in a cluster (cluster size) is directly related to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
158
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 148 publications
(167 citation statements)
references
References 115 publications
9
158
0
Order By: Relevance
“…Thus, LI joins a number of other manipulations that have parallel effects on these two measures (for a review, see Dwyer, 2012). Such results suggest that microstructural analysis of lick patterns and taste reactivity may be complementary measures that both assess taste palatability or hedonic responses.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, LI joins a number of other manipulations that have parallel effects on these two measures (for a review, see Dwyer, 2012). Such results suggest that microstructural analysis of lick patterns and taste reactivity may be complementary measures that both assess taste palatability or hedonic responses.…”
Section: Discussionmentioning
confidence: 99%
“…A cluster was defined as a set of licks, each separated by an interlick interval of no more than 0.5 s. This criterion was used by Davis and his coworkers (e.g., Davis & Perez, 1993;Davis & Smith, 1992) and in the majority of our previous studies using lick analysis techniques (for a review, see Dwyer, 2012). Although other criteria have been used (e.g., Dwyer, Pincham, Thein, & Harris, 2009;Spector, Klumpp, & Kaplan, 1998), parametric analyses suggested that there is little practical difference between them, as most pauses greater than 0.5 s are also greater than 1 s (e.g., Davis & Smith, 1992;.…”
Section: Apparatus and Stimulimentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, when rats consume an unpalatable solution (such as quinine), lick cluster size bears a negative monotonic relationship with the concentration of the solution (Hsiao & Fan, 1993;Spector & St John, 1998). This has led to the idea that lick cluster size measures can be used as a reliable index of stimulus palatability and, hence, the affective component of reward value (see Dwyer, 2012, for a recent review). Critically, lick cluster size is at least partially independent of consumption, which typically displays an inverted U-shaped function between concentration and total consumption, with intermediate concentrations of palatable solutions eliciting the highest levels of intake (e.g., Richter & Campbell, 1940).…”
mentioning
confidence: 99%
“…Critically, lick cluster size is at least partially independent of consumption, which typically displays an inverted U-shaped function between concentration and total consumption, with intermediate concentrations of palatable solutions eliciting the highest levels of intake (e.g., Richter & Campbell, 1940). As reviewed by Dwyer (2012), the dissociation between the two measures has been confirmed through flavor preference and aversion conditioning studies, which have demonstrated that some manipulations can influence lick cluster sizes, while leaving total consumption unchanged, and vice versa. Furthermore, it has been demonstrated that some taste aversions result in changes in lick cluster size that are analogous to actually changing a pleasant-tasting solution to an aversive one, while flavor preference conditioning result in changes that are analogous to changing the solution from a neutral to a palatable taste.…”
mentioning
confidence: 99%